Analyzing the interaction between actions and arguments in partial order planning - García, Diego R. (2006)
This research line involves the study of the interaction of arguments and actions when they are combined to construct plans using Partial Order Planning techniques. When actions and arguments are combined new types of interferences appear in the plans. This interferences need to be identified and resolved in order to obtains valid plans.